Recreating Collective Memories of Africa in the Afro-Caribbean Diaspora - Stephane Martin Demers (Caribbean Studies Students' Union, 2022)
Forced to succumb to a life of enslavement, African-turned-Afro-Caribbean slaves devel- oped a collective image of their beloved homeland and forged an unbreakable chain of solidarity among their many ethnicities. The collective recreation of Africa as manifest in the imagination of Afro-Caribbean slaves through the practice of Cuban Santería and Haitian Vodou in sixteenth- to eigh- teenth-century Cuba and Haiti catalyzed their resistance to European subjugation. In partic- ular, these recreated cultural memories served as a foundation for the enslaved to subvert the dominant culture and resist enslavement. Syncretism fails to properly acknowledge the Afro-Caribbean slaves' efforts in challenging the imperial regime and the role these efforts played in maintaining their African roots. The tumultuous yet hopeful history through which Cuban Santería and Haitian Vodou evolved reveals that the African spirit continuously takes on new forms but never dies.